Elementary school teachers' understanding of the mean during ongoing professional training - Soledad Estrella (Universidad Autónoma de Baja California, 2016)
This paper analyzes the open responses to a problem situation used in research on the mean with data containing outliers. The results reveal correct and incorrect perceptions and show that statistical notions regarding the context and representativeness of a data set are far removed from teacher training. Elementary teacher educators could draw from these perceptions and help to improve them so that future teachers may gain a full understanding of the concept, which will give them the skills they need to teach statistics in schools.